A fisiologia da interpretação no pensamento de Nietzsche - Santos , Ray Renan Silva (2017)
This work aims at analizing the notions of physiology and interpretation in Nietzsche’s philosophy. To this purpose, since Nietzsche did not propose a systematic study concerning such notions, our task consists in exercising the activity of interpretation. As we investigate about what interpretation really is, interpretation itself is thus made present, showing itself in the course of our text. All interpretation is located in a “place” from which its effectuation is possible, and every place expresses a difference, a singularity. This difference is related to the physiological constituition of the world as will to power. Given that the world realizes itself from and while a plurality of wills, each will is regarded as a specific and complex configuration that aims to domain, which has to do with optical point, this is, perspectivism, interpretation from which who interprets does it through his own perception. However, who interprets? Should we presuppose a “that” or a “who” as if there was an interpreting agent? Since the world is a plurality of wills, the logical-metaphysical perspective is shown as value assignment, as a means by which wills intensify their power interpretively. It is from the development of such assumptions that all our research will have its unfoldings.